DESENVOLVIMENTO DE MUDAS DE CAFEEIRO CONILON EM DIFERENTES RECIPIENTES E SUBSTRATOS - Felberg, Hellysa Gabryella Rubin (2021)
Conilon coffee is the most planted coffee species in Espírito Santo, occupying a prominent share for exports and domestic consumption, in addition to contributing to the generation of jobs and profitability in the field. Considering the importance of seedlings in the formation of coffee crops, since quality substrates associated with smaller volumes of containers in the production of Conilon coffee seedlings can influence the cost and the determination of the productive genetic potential, the objective was to evaluate the growth and initial vegetative development of coffee seedlings and foliar nutritional contents of the clonal variety Vitória Incaper '6V', produced under different containers and substrates. The experiment was carried out in a commercial nursery, located in Jaguaré, in randomized blocks, arranged in a 4x3 factorial scheme, with four replications, totaling 48 plots, with 13 plants per plot. There were four models of containers: conical bottom tube (280mL), inverted bottom (280mL), flat bottom (280mL) and polyethylene bag (20cmx11cm) and three substrates: Vida Verde®, Basaplant® and Biomix®. Weekly evaluations of plant height (ALT) and stem diameter (DIAM) were carried out and, in the final stage of seedling, development was evaluated with biometric variables: number of leaves (NF), total chlorophyll (TC), leaf area (AF), shoot fresh mass (MFPA) and roots (MFRA), shoot dry mass (MSR) and roots (MSR), height to diameter ratio (RAD), shoot dry mass ratio and roots (RPAR) and Dickson's quality index (IQD). To diagnose the nutritional status of the seedlings, leaf analysis was carried out in an agronomic laboratory, with all leaves obtained from the 13 sampling units of each plot at the end of the experiment. Data were submitted to analysis of variance using Tukey's test (p<0.05). Regarding the characteristics of leaf area, fresh and dry mass of the shoot, it is stated that these are dependent on the container and substrate, adverse occurs for the values of diameter, total chlorophyll and the relationship between shoot and root, which are not are influenced by such factors. The containers used significantly influence the characteristics of height and number of sheets, highlighting the polyethylene bag with a higher development than the tubes, but not statistically differing from the flat and conical tubes, respectively. In all characteristics significantly influenced by the substrates, Biomix® outperformed its averages. The seedlings obtained an average IQD of 0.58 and are all suitable for further development in the field. Polyethylene bags with the Biomix® substrate are recommended for the production of Conilon clone '6V' coffee seedlings, since they showed a better pattern of biometric development. And due to the foliar concentration of nutrients, I would recommend the use of tubes associated with the substrate Vida Verde® or Basaplant®.